Media Pembelajaran Bahasa Indonesia Menggunakan Aplikasi Canva Di SMAN 1 Rambah Samo - Prima, Riky; Mulyarjo, Mulyarjo; Setiawan, Agung; Chandra, Detri Amelia (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2023)
This journal article is a study using a qualitative descriptive approach. In this discussion, he will use the Canva application as a medium to learn Indonesian with SMAN 1 Rambah Samo using the Canva application. Learning media are the most important and useful tools for teachers in the classroom. In addition to using lecturing methods and books, teachers are also expected to have their own different learning media, and can also customize materials and conditions for each student. With the development of increasingly sophisticated technology, teachers need to be able to use technology as a learning medium. Teachers can use technology-based learning media as learning media and materials. One of which he uses her Canva application. Canva is an easy-to-access and use online application with a lot of attractive designs such as features, templates and categories that this application offers. This application has so many interesting and diverse designs that make the teaching and learning process in the classroom look more fun and less boring. By using this application, teachers can teach science, creativity and skills to their students, and these mediums can also be used in various aspects of life.